ANALISIS FAKTOR YANG MEMPENGARUHI MINAT PESERTA DIDIK DALAM MELAKUKAN AKTIVITAS KEBUGARAN JASMANI DI SMP MUHAMMADIYAH 4 SAMBI BOYOLALI - Setia Budi, Taufik; Nur Subekti; Nurhidayat Nurhidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to determine student’s interest in participating in physical fitness activities at SMP Muhammadiyah 4 Sambi Boyolali. This study is a quantitative descriptive study using a survey method, with data collection techniques employing a questionnaire as the instrument and measuring using a Likert scale. Based on the data results and the conclusions of this study. It was found that among students interests in participating in physical fitness activities at SMP Muhammadiyah 4 Sambi Boyolali, the extrinsic factor of facilities and infrastructure received the highest score, with 50% strongly agreeing; followed by the intrinsic factor of maintaining health, with 47% strongly agreeing; and the intrinsic factor of personal motivation, with 40% strongly agreeing.